Purification and characterization of glutamate decarboxylase from Aspergillus oryzae NSK - Lee, Audrey Ying Yeng (2014)
γ-Amino butyric acid (GABA) is a major inhibitory neurotransmitter of the mammalian central nervous system that plays an important role in regulating vital neurological functions. The enzyme that is responsible for GABA production is glutamate decarboxylase (GAD), an intracellular enzyme that both food and pharmaceutical industries are currently used as the major catalyst in biotransformation process of GABA. Recently, a novel strain of Aspergillus oryzae NSK with high GABA biosynthesizing capability was successfully isolated from a soy sauce koji in Malaysia. To gain a detailed insight of the GABA producing capability of the strain, an effective isolation and purification procedure of glutamate decarboxylase (GAD) were developed. Mechanical disruption by sonication, which yielded 1.99 U/mg of GAD, was by far the most effective cell disintegration method compared with the other extraction procedures examined, which include solvent permeabilization and enzymatic lysis. Further optimization of the sonication protocols successfully increased the yield of GAD by 176% from 1.99 U/mg to 3.50 U/mg. After extraction of GAD, it was purified to 21-fold with a recovery of 11.60% using a combination of 30-70% ammonium sulphate precipitation followed by liquid chromatography techniques comprising reverse (Flow-through) mode ion exchange chromatography (DEAE- Sepharose FF) and twice gel filtration using Superdex 200 HR 10/30 column. An electrophoretic study showed that the purified GAD exists as a hexameric structure under native conditions with an estimated molecular weight of 240 kDa and 38 kDa of subunit molecular weight. It is thermally stable between 0- 40˚C and was found to be optimally active at 55˚C and pH 5.5. The Km and Vmax values calculated were 10.18 mM and 5.15 U/ml/min, respectively. Activity of the enzyme was significantly reduced by FeCl3 (62.14%) and sulfate minerals in the following order: MgSO4 (66.32%)> (NH4)2SO4 (73.29%)> NaSO4 (80.96%) > CuSO4 (81.64%). An excellent stability of GAD over a wide pH range offer high potential application in food industries to produce various GABA-enriched fermented foods using a GRAS (Generally Regarded as Safe) fungal source. Current study provided a detailed insight of the characteristics of GAD from A. oryzae NSK in order to achieve maximum catalytic capacity of the GAD during production of GABA-enriched food and also demonstrating a feasible alternative method of GAD purification.